(untitled) (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2023)
The objective of this text is to understand the relationship between the configuration of masculinity and the spatialities instituted by drug trafficking. Specifically, the focus is on understanding how the elements that make up masculinity (for a given social group) are activated in a type of "performance" of masculinity that is linked to those instituted spatialities. The methodology used is based on the analysis of discursive content (Bardin 1977) and the crossing of each discursive category identified with a spatial reference (Gomes, 1993), as proposed in Silva & Silva (2016) and Autor (2019). The results indicate that physical violence expressed in fights and the use of certain drugs are linked to a performance or conduct that is configured in an assembly between the lived spatialities, the power relations involved, the daily practices of the bodies and also, the hegemonic masculinity established in the group of belonging.